Discussing the Need to Manage Uncertainty Relating to Users in Road Tunnel Fire Risk Assessment - Panagiotis Ntzeremes; Konstantinos Kirytopoulos; Vrassidas Leopoulos (Journal of Risk Analysis and Crisis Response (JRACR), 2020)
Although tunnels provide roads with numerous advantages, they also include significant risks. Especially, fire accidents are the biggest threats. Nowadays, risk assessment has the predominant role for managing tunnel fire safety and users are in the centre of attention. However, existing methods exhibit lack in treating uncertainty stemming from users. This paper aims to discuss current ways of representing tunnel users’ uncertainty as well as to introduce the importance of distinguishing these representations in the wider context of risk assessment.